ASPEK BIOLOGI PERIKANAN IKAN LAYANG (Decapterus Macrosoma) YANG TERTANGKAP DENGAN BAGAN RAMBO DI PERAIRAN PANTAI SUMPANG BINANGAE KABUPATEN BARRU - Hasrun Hasrun; Kasmawati Kasmawati (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2021)
Flying fish is one of the dominant pelagic fish caught and has high economic value in Sumpang Binangae Waters. This fish is caught by many chart rambo fishing gear. The purpose of this study was to determine the biological aspects of flying fish especially those caught in the waters of Sumpang Binangae, Barru Regency. This research will be conducted for four months, from May 2020 to August 2020, which is located at the Sumpang binangae Fish Landing Base, Barru district. Identification of flying fish species is done visually by looking at the color and body shape and special characteristics based on the Guidelines for Practical Identification of Small Pelagic Fish Species in Figure, Suwarso, 2010, The composition of the type of catch is calculated based on the amount of catch (tonnes). Sex ratio, TKG, (Walpole 1993), Length of First-Time Gonads of Fish (Lm)The results showed that based on the composition of the types of fish caught, the percentage of the dominant catch was 27.41% mackerel (Rastrelliger kanagurta), 24.26% flying fish (Decapterus macrosoma), 23 anchovies (Stolephorus sp). 28%, squid (Loligo sp) by 2.24%, flying fish (Cypselurus sp) by 8.98% and tembang fish (Sardinella fimbriata) by 13%, while the type of flying fish caught was only one type, namely white-tailed flying fish. slightly yellowish (Decapterus macrosoma). Comparison of the number of male and female sex, it was found that the sex ratio of male and female Layang fish (D. macrosoma) was 52.83%: 47.17% or 1.12: 0.89, l. The size of the first maturity of male flying fish gonads in Barru waters is at the size of 15.68 cm or 156 mm and the female is at the size of 15.62 cm or 156 mm, while the male and female fish that are immature gonads are more than the fish that are mature gonads.